2010
DOI: 10.1016/j.niox.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral nitrite ameliorates dextran sulfate sodium-induced acute experimental colitis in mice

Abstract: Inflammatory bowel diseases (IBDs) such as Crohn's disease and ulcerative colitis are chronic inflammatory disorders of the intestinal tract with excessive production of cytokines, adhesion molecules, and reactive oxygen species. Although nitric oxide (NO) is reported to be involved in the onset and progression of IBDs, it remains controversial as to whether NO is toxic or protective in experimental colitis. We investigated the effects of oral nitrite as a NO donor on dextran sulfate sodium (DSS)-induced acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
1
27
2
Order By: Relevance
“…23,24) Large quantities of NO are known to be generated in the stomach by the non-enzymatic acid reduction of salivary nitrite, in addition to the NO generated enzymatically by NO synthase from L-arginine, and have been proposed to exert various physiological functions in the gastrointestinal tract [35][36][37][38] including as a barrier in the stomach. [39][40][41] Therefore, it is possible that the NO generated in the stomach Snitrosylates Gal-2 to sustain a stronger barrier through the crosslinking of mucins and to prevent the oxidative inactivation of Gal-2.…”
Section: Discussionmentioning
confidence: 99%
“…23,24) Large quantities of NO are known to be generated in the stomach by the non-enzymatic acid reduction of salivary nitrite, in addition to the NO generated enzymatically by NO synthase from L-arginine, and have been proposed to exert various physiological functions in the gastrointestinal tract [35][36][37][38] including as a barrier in the stomach. [39][40][41] Therefore, it is possible that the NO generated in the stomach Snitrosylates Gal-2 to sustain a stronger barrier through the crosslinking of mucins and to prevent the oxidative inactivation of Gal-2.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that dietary supplementation with nitrite ameliorated DSS-induced colitis, possibly by bypassing NOS activity and using an alternative mechanism of NO generation involving the reduction of nitrite (Lundberg and Weitzberg, 2009;Ohtake et al, 2010). Our study examined the effect of modulating BH4 levels by dietary pretreatment of animals with sepiapterin (SP), a metabolic precursor of BH4, thereby enhancing the NO-sGC-PKG pathway and abrogating DSS induction of colitis and CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ohtake et al (10) reported that oral administration of nitrite ameliorated DSS-induced colitis. Moreover, to our knowledge, there is no report indicating that nitrite itself aggravates DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 99%